Rainwater tank systems for urban water supply design, yield, energy, health risks, economics and social perceptions - Sharma, Ashok K. (Ashok Kumar) 1956-; Begbie, Donald; Gardner, Ted (IWA Publishing, 2015)
The book is suitable for use at undergraduate and post graduate levels and is of particular interest to water professionals across the globe, who are involved in the strategic water planning for a town, city or a region.